Material flow analysis of mercury and zinc in Jeram sanitary landfill / Nurhawa Abdul Rashid - Nurhawa , Abdul Rashid (2017)
In this research, two heavy metal (Hg and Zn) flow was identified by using Material Flow Analysis (MFA) modelling. Field sampling and heavy metal analysis were carried out for six months in a sanitary landfill located in Selangor. Interview sessions with stakeholders were done to gain additional data. All heavy metal analysis was carried out based on USEPA Method 200.8 standard, activated iodated charcoal traps and general emission equation model. STAN 2.5 software was utilized to perform MFA models in this study. Total waste received in Jeram Sanitary Landfill in 2014 was 839,500 tonne. 37.7% of waste received composed of food waste and 4% was household hazardous waste. A comparison between current waste flow analysis and estimated waste analysis under two different scenarios were generated. Results indicated that if the national recycling rate of 22% is achieved and the amount of waste to be recovered in the MRF can be increased to 400 tonne/day, total amount of waste that can be recovered from this landfill will increase from 10,949 tonne/year to 87,600 tonne/year. Estimation of economic value of current recyclable waste deposited in this landfill was also explored. Finding shows that total amount of potential profit was approximately RM 55 million or 12 million USD per year. Total input of material into the landfill system was 3 million tonnes per annum and total material exported from the system was 1 million tonnes per annum. Completed Hg flow revealed that the input of Hg into the landfill system was 1962 kg/year, the output was 2.3 kg/year and the stock of Hg that remained inside the landfill was 1960 kg/year. Inputs of Hg into the systems were from MSW received by the landfill (1897 kg/year), clay material which was used as the soil cover (65 kg/year) and also precipitation (0.04 kg/year). Hg was released to the environment as output through landfill gas (0.004 kg/year), working face (0.32 kg/year), treated leachate (1.54 kg/year) and surface runoff (0.42 kg/year). Meanwhile, the input of Zn into the landfill was from waste deposited (11,400 kg/year) and soil cover (7,211 kg/year). Outputs of Zn identified in this system were surface runoff (32 kg/year) and treated leachate (3 kg/year). Thus, these MFAs can be used as a supporting tool for the authority to start implementing necessary actions to reduce heavy metal accumulation in sanitary landfill system.